On the projected increase of Sahel rainfall during the late rainy season. (4th February 2016) - Monerie, Paul‐Arthur; Biasutti, Michela; Roucou, Pascal
ABSTRACT: Thirteen CMIP5 models are used to analyse changes in climate over the West African monsoon region between the near future (2031–2070 under the RCP4.5 emission scenario), and a control period (1960–1999 under the historical emission scenario), with a focus on the late rainy season. The monsoon circulation is projected to strengthen and to shift northward leading to more rainfall during the Sahelian season. The results show an increase of the Rainfall amounts in September–October and a delay in the monsoon withdrawal. The increased moisture that fuels the rainfall anomalies is associated with an increase in moisture flux convergence and with local moisture recycling. The moisture transport dominates the water budget change in September while the local recycling is prominent in October. The delay in monsoon withdrawal, although expected from the increase in rainfall in September–October, is not strongly correlated with the size of the monthly anomalies.